Consumer Welfare and Energy Supply Shocks Induced by Armed Conflicts: Evidence from Europe - Ján Buleca; Maryna Tatar; Ermanno Affuso; Jr. Franklin G. Mixon (Peace Economics, Peace Science and Public Policy, 2026)
Abstract In the context of increasing global geopolitical instability, this study examines the association between worldwide armed conflict exposure and household energy market outcomes in Europe. Using annual panel data for 29 European countries over 1995–2021, household energy supply and demand are estimated within a two-stage dynamic panel framework employing the Difference Generalized Method of Moments estimator. Global armed conflict exposure is measured as the annual count of armed conflicts worldwide, serving as a common external conflict exposure metric for European energy markets. The results indicate that higher global conflict exposure is negatively and statistically significantly associated with household energy supply. Consequently, an equilibrium displacement model translates these market responses into consumer welfare effects. In the short term, assuming a one-year dynamic adjustment, each additional armed conflict worldwide is associated with a consumer surplus loss of approximately EUR 11.1 million for a representative European country, with cumulative panel losses reaching approximately EUR 31 billion by 2021.